Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-02-10T18:32:51+01:00
A.) x-3x +2-2x-7=-4x-5
b.)-5x+4y-y-7x-9y=-12x-6y
c.)4x+5-x-4+x-3x=x+1
d.)0,5a-2a+9-0,5a-11,5=-2a-2,5
e.)-14k+9k-13+k+3+4k=-10
f.)-3k+2m+5m+5m-7+k-m=-2k+11m-7
g.)2x-4+3x-2=5x-6
h.)x-3y-2x+6y=-x+3y
i.)2y-5-3y-4-8y+9=-9y
2 5 2
2010-02-10T18:35:48+01:00
A.) x-3x +2-2x-7= -4x -5
b.)-5x+4y-y-7x-9y= -12x -6y
c.)4x+5-x-4+x-3x= x -1
d.)0,5a-2a+9-0,5a-11,5= -2a -2,5
e.)-14k+9k-13+k+3+4k= -10
f.)-3k+2m+5m+5m-7+k-m= -2k +11m -7
g.)2x-4+3x-2= 5x -6
h.)x-3y-2x+6y= -x +3y
i.)2y-5-3y-4-8y+9= -9y
2010-02-10T18:38:20+01:00
A)x-3x+2-2x-7=-4x-5
b)-5x+4y-y-7x-9y=-12x-6y
c)4x+5-x+4+x-3x=x+9
d)0,5a-2a+9-0,5a-11,5=-2a-2,5
e)-14k+9k-13+k+3+4k=-10
f)-3k+2m+5m+5m-7+k-m=-9k+11
g)2x-4+3x-2=5x-6
h)x-3y-2x+6y=-3x+3y
i)2y-5-3y-4-8y+9=-13y